Ketika Informalitas Bertemu Kemiskinan: Kerentanan Pekerja Informal di Perdesaan dan Perkotaan di Sumatera Utara - Rolinta Damanik; Hasrat Ifolala Zebua (Jurnal Ketenagakerjaan, 2025)
The province of North Sumatra, with its 33 districts/cities, faces significant challenges in managing the informal sector, where a high proportion of the workforce is employed compared to the formal sector. This study aims to analyze the vulnerability of informal workers to poverty in the region, focusing on demographic characteristics, economic factors, and regional disparities. The research employs ordinal logistic regression analysis to identify key determinants of vulnerability to extreme poverty among informal workers. The results show that informal workers, particularly in rural areas, are more likely to experience poverty, with factors such as low education levels, limited access to financing (especially microcredit), lack of luxury goods, short working hours, and marital status being significant contributors. Workers in urban areas have better access to formal sector jobs and are less vulnerable, while those in rural areas are highly dependent on the informal sector with limited opportunities for economic advancement. The study concludes that improving access to financing, education, and employment opportunities in rural areas can reduce the vulnerability of informal workers to poverty. Additionally, policies supporting the growth of the formal sector in rural areas and enhancing social safety nets are essential for reducing economic disparities.